INTELLECTUAL SYSTEMS: PRINCIPLES OF THE HEURISTIC SELF-ORGANIZATION OF THE PROCESSES OF SENSE THINKING AND SENSE ACTIVITY - Серій Ілліч Доценко (Радіоелектронні і комп'ютерні системи, 2020)
The purpose of this study is to solve the following problems. The first task concerns the determination of the form of correspondence of factors that model the technological activity of the “process” and “resource” with factors that are subjected to simultaneous processing according to the central regularity of the integrative activity of the brain. The second task concerns the determination of possible forms of relationships for technological activity factors “process” and “resource” with concepts that characterize thinking processes, namely: “reflection”, “data”, “information”, “knowledge”, “meaning”, “thinking”, “intelligence”, “semantic thinking”, “understanding”. From the above analysis of the problems of representation, processing, and acquisition of knowledge, it follows that the main problem is the mismatch of the laws of formal logic with logic, which is realized in the thinking processes of living beings. Human intelligence in the theory of artificial intelligence is perceived as an auxiliary tool. In the theory of artificial intelligence, the model of an artificial neuron copies its structure but does not reproduce the processes that are realized in it. From a philosophical point of view, the basic concepts that reveal the content of thinking processes are the concepts of “reason” and “mind”. Moreover, the main property of the mind is its dialectics, which is manifested through the concept of "measure". The content of the concept of “measure” is defined in the form of a dialectical unity of the concepts of “general” (qualitative definition) “single” (quantitative definition). The methodological basis for the construction of all logical models is the methodology of a holistic approach based on which a logical model of holistic semantic activity is formed. In this model, the content of "duality" of the content of the concept of "activity" is disclosed. This ensured the definition of the principle of organizing the intellectual system into an organized whole in the form of the dialectical unity of certain tasks, as well as the principle of self-organization of its activities in the form of a mechanism to ensure compliance with the results of solving these problems. Based on the hypothesis about the equivalence of the technological activity of the natural intellectual system using the “process” and “resource” factors and the process of semantic thinking based on the central regularity of the integrative activity of the brain, a logical model for structuring excitations on the theory of functional systems has been developed. This model, along with the logical model of semantic activity (process), serves as the basis for the formation of logical models of levels 0 - 4. The principle of heuristic self-organization in the form of a fourth heuristic, namely, dialectical self-organization for the concepts of “general” “single”, is a fundamental principle of heuristic self-organization of pairs of factors for logical models. The architectures of these logical models are formed using two pairs of factors defined for each model. The fifth principle of heuristic self-organization follows from this: the architecture of logical models of semantic thinking and semantic activity are formed using two pairs of factors defined for each logical model, the elements of each of which are connected by cause-effect relationships, which in meaning correspond to pairs of process and resource factors, and correspond to the architecture of the Cartesian coordinate system.